A Study of Regenerative Tourism in Strengthening the Sustainability of Surabaya's Old City as an Urban Heritage Area - Retno Juwita Sari; I Wayan Putra Aditya (Faculty of Economics and Business, University of Mataram, 2026)
This study examines the role of regenerative tourism in strengthening the sustainability of Surabaya Old City as an urban heritage area facing physical degradation, spatial conversion, and limited community participation. This study aims to analyze the role of regenerative tourism in strengthening the sustainability of the area. Using a qualitative approach, data was obtained through observation, literature review, and interviews. Data analysis was conducted thematically by grouping findings based on environmental, social, cultural, and economic. The findings reveal that regenerative tourism supports the conservation and adaptive reuse of heritage buildings, enhances community empowerment through MSME and local stakeholder involvement, strengthens historical narratives and cultural activities, and stimulates a heritage-based creative economy that improves local welfare. In conclusion, this study lies in integrating regenerative tourism with urban heritage sustainability in the context of Surabaya Old City, highlighting tourism not only as a preservation strategy but also as a restorative and community-centered development approach. This research contributes to sustainable tourism studies by offering a holistic and participatory model for managing heritage destinations that are inclusive, resilient, and culturally meaningful.